Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Please show that for all $x,y\in\mathbb{R}$,

$$e^{x+y} - e^xe^y = \lim_{k\to\infty} \sum_{n=1}^k \sum_{j = 0}^n\left(\frac{x^{k+j}}{(k+j)!}\frac{y^{n-j}}{(n-j)!} + \frac{x^j}{j!}\frac{y^{k+n-j}}{(k+n-j)!}\right)\;.$$

(This is from a homework assignment)

I'm thinking of a way to proceed by induction, but it is not clear to me how to utilize it for this problem. Can someone work out this problem so I can ask questions from it?

share|cite|improve this question

Hint: The Taylor expansion for $e^x$ is

$$e^x=\sum_{n=0}^{\infty}\frac{x^n}{n!} =\lim_{M\to \infty}\sum_{n=0}^{M}\frac{x^n}{n!} \; .$$

So you can find the Taylor expansions for $e^{x+y}$ and $e^y$ as well. The rest is a matter of combining the series together to obtain $e^{x+y}-e^xe^y$.

See Martin's worked out solution.

share|cite|improve this answer
    
Thank you, I tried it out but am lost in this. can you please show how to do the problem? – mary Apr 1 '11 at 3:53
    
I runned through the algebra, but am not getting the answer above. Can someone please show how this? – mary Apr 1 '11 at 4:47
    
@user8917 Perhaps if you showed us your work, someone could point out what to do next. – Martin Sleziak Apr 1 '11 at 9:56

I've tried to do some computations. Although I did not obtain the required formula, I am posting it here - hopefully someone can either spot a mistake in what I did or modify the method to obtain the above result.

$$\sum\limits_{i=0}^k \sum\limits_{i=0}^k \frac{x^i}{i!} \frac{y^j}{j!}= \sum\limits_{m=0}^{2k} \sum\limits_{\substack{i+j=m\\0\le i,j \le k}} \frac{x^i}{i!} \frac{y^j}{j!}= \sum\limits_{m=0}^k \sum\limits_{\substack{i+j=m\\0\le i,j \le k}} \frac{x^i}{i!} \frac{y^j}{j!}+ \sum\limits_{m=k+1}^{2k} \sum\limits_{\substack{i+j=m\\0\le i,j \le k}} \frac{x^i}{i!} \frac{y^j}{j!} $$

The first sum:

$$\sum\limits_{m=0}^k \sum\limits_{\substack{i+j=m\\0\le i,j \le k}} \frac{x^i}{i!} \frac{y^j}{j!}= \sum\limits_{m=0}^k \sum\limits_{i=0}^m \frac{x^iy^{m-i}}{i!(m-i)!}= \sum\limits_{m=0}^k \frac1{m!} \sum\limits_{i=0}^m \binom mi x^iy^{m-i}= \sum\limits_{m=0}^k \frac{(x+y)^m}{m!} $$

The second sum:

$$\sum\limits_{m=k+1}^{2k} \sum\limits_{\substack{i+j=m\\0\le i,j \le k}} \frac{x^i}{i!} \frac{y^j}{j!}= \sum\limits_{n=1}^k \sum\limits_{\substack{i+j=k+n\\0\le i,j \le k}} \frac{x^i}{i!} \frac{y^j}{j!}= \sum\limits_{n=1}^k \sum\limits_{i=n}^k \frac{x^i}{i!} \frac{y^{n+k-i}}{(n+k-i)!} $$

The difference $e^xe^y-e^{x+y}$ is the limit of the last sum.

share|cite|improve this answer
1  
you made a small typo at the end, the sum over $i$ should be running from $n$ to $k$ since $n$ is smaller than $k$. – Raskolnikov Apr 1 '11 at 12:32
1  
@Raskolnikov Thanks a lot. Now, after your correction, I guess that if I compared the sum with $\sum\limits_{m=0}^{2k} \frac{(x+y)^m}{m!}$ instead of $\sum\limits_{m=0}^k \frac{(x+y)^m}{m!}$, I would get something which would be pretty close to the formula given by OP. (I am too lazy to do all the compatations again.) – Martin Sleziak Apr 1 '11 at 12:52
    
Yeah, I suppose something like that is going on. Since in the end, the goal is to show that the limit vanishes for $k \to \infty$, I don't think it really matters a lot what you compare it to. It's like choosing between $1-1=0$ and $3-3=0$. – Raskolnikov Apr 1 '11 at 13:19

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.